DEPENDENCE OF KNITTING MACHINE OPERATION DURABILITY ON NEEDLE DESIGN - ПЛЕШКО, СЕРГІЙ; КОВАЛЬОВ, ЮРІЙ (Technologies and Engineering, 2024)
Task. This research is focused on the accelerated durability testing of existing needles (item 0-388) of KO-type circular knitting machines and new needles suggested by the authors (Utility Model Patent of Ukraine No. 69369, 2012), and assessment of needle design effect on knitting machine operation durability. Method. Up-to-date methods of theoretical and experimental research were applied when conducting this research and solving its tasks. When analyzing the needle design effect on operation durability, an up-to-date accelerated testing technique for knitting machine needle durability was applied using a previously installed unit. Results. Operative parts of knitting mechanisms in a knitting machine are among the most critical elements that determine a knitting machine efficiency (machine productivity and quality of knitted fabric). The efficiency of knitting machines (productivity and quality of knitted fabric) largely depends on the faultless operation of critical parts in a knitting mechanism, particularly, the needles. When trying to increase the efficiency of knitting machines, special attention is paid to higher durability of needles as one of the pending problems in knitting machinery. The article considers analyzing the accelerated testing results of knitting machine needle durability: item 0-388 needles and a new design suggested by the authors, namely needles with grooves in the base and middle of the heel. The paper examines the influence of needle design on durability of its operation and confirms the feasibility of using new design needles in KO-type circular knitting machines instead of existing item 0-388 needles. The presence of grooves and an additional groove makes it possible to dampen the impact stress waves that arise in the body of the needle and to reduce their advance intensity from the heel to the hook and the latch holding unit. The analysis of research results led to the conclusions that the used technique and the accelerated testing unit for knitting machine needle durability make it possible to quickly and reliably assess the influence of the needle design on its operation durability. Scientific novelty. Development of scientific basis and engineering methods to design knitting machines. Practical relevance. The new needle design with grooves in the base and in the middle of the heel suggested by the authors (Utility Model Patent of Ukraine No. 69369, 2012) is functional and reliable in operation; the new needle design is almost 3.5 times more durable than that of existing item 0-388 needle.